Aproximación a la correlación de las fases lunares y el comportamiento del Frijol (Phaseolus Vulgaris L) Var.Allpa, en el distrito de San Roque de Cumbaza, provincia de Lamas. - Vecco Giove, Carlos Daniel (1998)
The peasant belief that the moon determines agricultural production is widespread. This work was done in the District of San Roque de Cumbaza (Lamas Province), had as main objective to determine the correlation of the lunar phases with growth, development and production of "Allpa-bean". A variety of common bean (Phaseolus vulgaris L.) of semitrepador habit, basic integral system of subsistence farming in the province, which is sown in function to the phases of the satellite. To this end, quantitative observations (weight, length, leaf area, number, etc.) and qualitative development, growth habit, pests, diseases, modulation were made; while the observation was made, registration of some meteorological factors such as temperature, humidity, precipitation, etc. All this was done with reference to the lunar phases. The statistical design was completely randomized, factorial analysis. Two factors were considered, the first is the environmental factor (A) levels Tingado (B), protected against rain and wind and open field (C), the second is the phase factor moles (D) with four levels corresponding each phase of the moon. In its main planting time mode. The experiment began with 26 experimental units on two plots (I and II) and developed under controlled conditions of soil and water. In general, the vegetative and reproductive development was favored in tinglado conditions. higher average yield for planting of the full moon, followed by the last quarter, the new moon and last quarter was obtained significantly. However, comparing the results with those obtained from previous experience the same that guides the present study, we infer with some caution, that the performance of frejol "allpa" will be greater when closer the planting at the beginning of the Bell. was also significantly observed that the shorter length of the main stem is recorded in planting Full Moon, increasing successively to the Quarter, featuring the largest lengths of the main stem when comparing the results with those obtained from the preliminary experience, the correlation coefficient for this trend is highly significant, on the other hand, in the vegetative stage, from the stage of primary leaf (V3), the shows performed observed significant differences for two groups of higher and lower leaf growth formed by the LM treatments LL-CC and CM, respectively. Analysis of agrometeorological factors acting between the crop strict relationship between average temperature, relative humidity and precipitation without spreading the extent to which these condition it was found. The response of the treatments. No significant changes were noted in the incidence of pests and diseases, or relationship between the appearance of mogolas of symbiotic fixation with respect to the lunar phases. The experiment revealed an unsuspected productive potential for variety "Allpa-bean", also obtaining data relevant to the characterization of such crops such as the length of the stages of development, growth habit, productive behavior, biometris, pests and diseases, among others